On the mixed reduction: an alternative axiomatization of the fuzzy NTU core - Wei-Shih Du, Pang-Tung Liu, Yu-Hsien Liao (Results in Nonlinear Analysis, 2020)
In the framework of fuzzy non-transferable-utility (NTU) games, Hwang [5] and Liao [6] introduced several extensions of reduced games and related consistency properties due to [3], Serrano and Volij [8] and Voorneveld and van den Nouweland [9] respectively. Different from the axiomatic results due to Hwang [5] and Liao [6], this paper is devoted to propose a mixed reduction and related consistency property to characterize the core on fuzzy non transferable-utility (NTU) games.